Ameloblastoma of the Jaw in Three Species of Rodent: a Domestic Brown Rat (Rattus norvegicus), Syrian Hamster (Mesocricetus auratus) and Amargosa Vole (Microtus californicus scirpensis). Issue 2 (August 2017) - Murphy, B.; Michel, A.; LaDouceur, E.B.; Bell, C.; Lin, M.; Imai, D.M.
Summary: Ameloblastoma is a locally aggressive tumour derived from the odontogenic epithelium of the developing tooth germ. This uncommon odontogenic tumour is generally considered benign, but rarely, both distant metastasis and cytological atypia occur and this malignant version is referred to as malignant ameloblastic carcinoma. Here we document a spontaneous malignant ameloblastic carcinoma in a rat ( Rattus norvegicus ) with metastasis to the submandibular lymph node. We also describe ameloblastomas in two other muroid rodents, an Amaragosa vole ( Microtus californicus scirpensis ) and a Syrian hamster ( Mesocricetus auratus ). To our knowledge, this is the first report of a malignant ameloblastic carcinoma in any animal and the first report of ameloblastoma in a vole and hamster.